(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The development of export potential is one of the key factors ensuring sustainable economic growth and competitiveness of industrial sectors. The textile industry plays an important role in the economy of many developing countries due to its high employment capacity and strong export orientation. Uzbekistan possesses significant opportunities for the development of the textile sector because of its rich raw material base, particularly cotton resources. This article examines the economic essence, structural components, and theoretical approaches to the formation of export potential of textile enterprises. Special attention is given to the analysis of export potential in the textile sector of Uzbekistan. The research identifies the main components of export potential, including production capacity, technological level, financial resources, human capital, and marketing capabilities. The study also highlights the role of government policy and institutional support in strengthening export performance. The findings suggest that effective management of internal resources and the implementation of modern technologies can significantly enhance the export potential of textile enterprises in Uzbekistan.